Training on Creating Educational Maze Media for Teachers to Support Children’s Fine Motor Skill Learning - Sinta Oktavianti; Laila Nursafitri (Yayasan Daarul Huda Kruengmane, 2026)
Teachers must have high imagination and creativity and be able to enhance engaging and enjoyable play activities, one of which is by using Educational Play Tools (EPT). The purpose of this study was to increase the variety of Educational Play Tools, specifically Maze Media, at TK and Kober Braja Asri. The method used in this community service activity was the Service Learning (SL) method, in which the mentoring team provided training and assistance in creating educational maze media from recycled materials to support fine motor skill learning for teachers at TK and Kober Braja Asri in two meetings. The activity was carried out in several stages: planning, implementation, and evaluation. The results showed that teachers participated enthusiastically, as this was their first training session on Maze Media Educational Play Tools. The teachers also successfully completed the creation of the media collaboratively in groups. Maze Media is a learning tool that can be used by teachers in classroom activities because it helps train hand–eye coordination, improves memory, and fosters cooperation.